Occurrence of diatom, pseudo-nitzschia spp. (bacillariophyceae) and related enviromental factors at Santubong and Samariang Batu estuaries in Kuching Division - Nemala, Nalathamby (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Pseudo-nitzschia spp. is the causative organism for Amnesic Shellfish Poisoning (ASP) due to its capability of producing Domoic Acid. Occurrence of Pseudo-nitzschia spp. is highly dependent on the environmental conditions. Therefore ecological studies of this harmful diatom have been crucial. This study is initiated to understand the temporal distribution of Pseudo-nitzschia spp. related to environmental stricture along with attempt to understand the correlation of ecological effect to their diurnal distribution. Studies were carried out at two locations of Samariang Batu estuarine and Santubong river estuaries, Kuching. Results showed fluctuations of cell abundance every fortnight and on daily distribution. Presence of Pseudo-nitzschia spp. had statistical correlation with temperature, rainfall abundance and enrichment of reactive phosphorus nutrient. Nutrients found to be present with statistical significance (p<0.05) at both locations were Nitrate, reactive Phosphate and silicate ranging in-between 0 -2.04 mg/L, 0.01 -0.48 mg/L and 0.0 -2.772 mgIL respectively .The highest cell count was obtained at Santubong in January 2011 recording 3.9 X 104 cells L-1 Highest cell recorded at Samariang Batu was 1.4 X 103 cells L-'. Diurnal samples showed clear relationship between cell abundance and salinity. Cell density peaked upon high tide cycle with high salinity though throughout sampling salinity fluctuated amid 6.1 -7.6. Other parameters lacked statistical evidence to be correlated with the distribution of Pseudo-nitzschia spp. nevertheless there are other intangible variables involved.